Mechanical process and size characterisation of rice husk, mango bark and mango leaves as a drag reduction additive - At-Tasneem, Mohd Amin; A. N., Oumer; W. H., Azmi; K., Sulihaakma (IOP Publishing, 2019)
In many drag reduction applications, polymer and organic fibre additives are mostly used because they alter the generation of turbulence at the core region. Nano-sized particles may able to reach the viscous region of the boundary layer and alter the internal turbulent structure near the wall. However, the challenge is that it is hard to find nano-sized organic particles in the market. This paper presents the preparation and characterisation of organicbased nanoparticles to be dispersed in a base fluid as drag reduction additives. Similar steps of nanoparticles preparation proposed by researchers were employed. The coarse powder of rice husk and raw samples of mango bark and mango leaves were ground using a domestic grinder. Then, the samples were further ground using planetary ball milling until reached nanoscale. The size of all samples was measured using Zetasizer. Then, all samples were ultrasonicated for three hours to de-agglomerate larger particles. It revealed that rice husk was able to produce 61% intensity of nanoparticles after four hours of the dry milling, five hours of wet milling and three hours of ultrasonication. The mango bark and mango leaves formed the maximum of only 6.7% and 4% intensity of nanoparticles after seven hours of wet milling and three hours of ultrasonication, respectively. However, mango bark and mango leaves remain stable after two months of observation, and rice husk showed significant sedimentation after two weeks of idle time.